The Influence of Motivation on the Performance of Civil Servants at UPT Puskesmas Pulo Brayan in 2023 - Toji Hamonangan Nasution; Masdalina Pane; Agnes Purba (SEAN Institute, 2023)
Performance is defined as success in completing duties, both in terms of quality and quantity. The performance of health workers reflects the quality of health services, which contributes to public satisfaction. Motivation is the main factor that influences the performance of health workers. A strong motivation influences individual behavior in various contexts, including in learning and working. The objective of this research is to determine the effect of motivation on ASN ( State Civil Apparatus ) performance in UPT( Integrated Service Unit ) Puskesmas ( Community Health Center ) Pulo Brayan in 2023. This is a quantitative survey research design with a cross sectional approach. The number of samples is 31 State Civil Apparatus using a total sampling technique. The data are collected by a questionnaire and they are analyzed with univariate, bivariate and multivariate analysis. The results of the research show that there is an effect of motivation on the performance of the ASN in Puskesmas Pulo Brayan in terms of extrinsic motivation (p-value = 0.026) and intrinsic motivation (p-value = 0.000). Age has no effect on the performance of the ASN in Puskesmas Pulo Brayan (p-value = 0.556), neither length of work on performance of the ASN at the Pulo Brayan Community Health Center (p-value = 0.954). The most dominant variable in this research is intrinsic motivation with OR = 28.000. It is suggested that Puskesmas continue to improve and sustain the motivation so that the ASN’s performance can affect the service and patient/visitor satisfaction. Community Health Centres need to encourage the employees to strengthen relationships and collaboration among members of ASN.